PENGARUH LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR EKONOMI KELAS X MA KHULAFAUR RASIDIN KUBURAYA - Febryanto, Arie; Witarsa, Witarsa; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine whether there is an effect of learning environment on learning outcomes of class X in MA Khulafaur Rasidin Kuburaya.. The form of this research was quantitative research with the type of research ex-postfacto. The sample in this study was the X class of MA Khulafaur Rasidin Kuburaya, which amounted to 45 students. The data analysis technique used a simple linear regression test with the help of the SPSS version 16.0 program. The results of this study indicated that 9% of students in the high category, 73% of students in the medium category, and 18% students in the low category. While learning outcomes of student in X class in MA Khulafaur Rasidin indicated 42% of students in the completed category, 58% of students in the not completed category. There was a positive influence between learning environment on learning outcomes of students with a regression equation Y = 23,051 + 0,749X. The results of hypothesis testing compared to significance value wot 0.05,it can be seen that the significance value of 0,001 < 0.05 that means (H0) is rejected and (Ha) is accepted, means that it had a influence between learning enviroment on learning outcomes in X Class in MA Khulafaur Rasidin KuburayaKeywords: effect of learning environment, learning outcomes